Assessing evidence-based medicine and opioid/barbiturate as first-line acute treatment of pediatric migraine and primary headache: A retrospective observational study of health systems data - Seng, Elizabeth K; Gelfand, Amy A; Nicholson, Robert A (Cephalalgia, 2019)
To evaluate providers' use and predictors of evidence-based medicine or opioid/barbiturate as first-line acute treatment for children's initial presentation of acute migraine or primary headache. This retrospective, observational study utilized patient (children ages 6-17) and provider/encounter characteristics extracted from the patient's Electronic Health Record from 2008-2014 during an initial encounter for migraine or primary headache. The primary outcome was provider evidence-based medicine utilization; overall prescriptions and opioid/barbiturate prescriptions were also evaluated. Hierarchical linear modeling examined whether Level 1 (patient: Demographic, insurance type) and Level 2 (provider/encounter: Treatment setting/location, encounter diagnoses) characteristics influenced outcomes. In all, 38,926 patients (56.7% female, mean age = 12.1) and 1617 providers were evaluated. Only 17.7% of patients were diagnosed with migraine; 16.1% received evidence-based medicine. Older children (OR = 1.07, < 0.001), females (OR = 1.14, < 0.001), and those diagnosed with migraine (OR = 4.71, < 0.001) were more likely to receive evidence-based medicine. Among prescriptions, 15.8% were for opioids/barbiturates. Older children (OR = 1.14, < 0.001) and those cared for in the emergency department/urgent care (OR = 2.02, < 0.001) were at increased risk. Demographics and migraine diagnosis are associated with evidence-based medicine and opioid/barbiturates. Primary care provides an opportunity to target provider interventions to enhance effective pediatric headache treatment.